Cluster Analysis of Low, Medium and High Social Welfare Effect Groupings in Malang City - Arifin, M Tafana Imania; Putri Sayekti, Azzahra Mubyaring; Cahyono, Jordan Putra (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2024)
Malang City is one of the cities in Indonesia that is facing the problem of poverty. One of the efforts made by the Malang City government is to provide Family Hope Program (PKH) assistance aimed at improving community welfare. In order for the allocation of assistance to be evenly distributed and directed, it is necessary to group villages based on the social welfare of the community through PKH data. This study aims to group Malang city villages based on PKH using average linkage clustering, obtained three clusters with low, medium and high social welfare. Clusters with high social welfare consist of 54 urban villages and get a lot of PKH assistance. Clusters with low social welfare consist of 2 urban villages and get little PKH assistance. Meanwhile, there is 1 urban village with low social welfare and little PKH assistance. Keywords: Average Linkage, Poverty, Social Welfare, Malang City